KAJIAN PERKEMBANGAN ARSITEKTUR POSTMODERN PADA BANGUNAN KOTA MEDAN - Br Ginting, Yeshi Ulina Utami; Pane, Imam Faisal (Jurnal Koridor, 2017)
Architecture is kind of culture product and civilization in form as a building. Beside the main function as an activities for user, architecture is a result of creativity, taste and human initiative in response from socio-cultural condition in a locality community. Post-modern is an architectural style that mixed tradition with the past, and rising style of architectural regionalism. Based on this style, the shape of building fully released and handed over to local architects. To express themselves and be creative on the shape and contents of the building at the regional point they stand. Based on backround, this study will examine is there a building in Medan which responds to the development of post-modern architecture. This study case is based on a literature study with methods such as inventory, descriptive, analysis and interpretation. The results showed that the post-modern architectural concept evolved and applied to new buildings in Medan.